Genetic diversity of reintroduced tree populations in restoration plantations of the Brazilian Atlantic Forest - Zucchi, Maria I.; Sujii, Patricia S.; Mori, Gustavo M. [UNESP]; Viana, João P. G.; Grando, Carolina; Silvestre, Ellida de Aguiar; Schwarcz, Kaiser D.; Macrini, Camila M.; Bajay, Miklos M.; Araújo, Fabiano L.; Siqueira, Marcos V. B. M.; Alves-Pereira, Alessandro; et al. (Wiley, 2018)
Long-term ecological success of large-scale restoration programs planned for the next decades will rely on genetic diversity (GD) of reintroduced or colonizing species, a limiting factor in highly fragmented landscapes. In small and isolated natural remnants or restoration areas, substantial reduction in population's size or connectivity may lead to local extinctions due to the accumulation of deleterious recessive alleles and ongoing reduction of fecundity, plant vigor, recruitment success, and adaptive potential. Despite the paramount role of GD for species persistence, its levels in restoration programs are poorly known. We assessed the GD of four model tree species (different succession stages, dispersal, and pollination syndromes) from the Brazilian Atlantic Forest, comparing two high-diversity restoration plantations, one forest fragment and one conserved remnant. Contrary to the expectation that the plantation strategies adopted in the restoration programs could result in genetic composition homogenization, we found that restoration areas established heterogeneous genetic groups with similar levels of neutral GD and inbreeding to those observed in natural forest remnants. This pattern was consistent across the four functionally different tree species, despite some species idiosyncrasies. For instance, we observed lower allelic richness in early successional species in restoration sites, suggesting that some species may be more prone to reintroduction with lower GD. Thus, we advocate the use of high GD levels in restoration to support biodiversity conservation in human-modified landscapes, thus reinforcing the role of ecological restoration for recovering the diversity of genes—the basic constituent of biodiversity.
Keywords: conservation genetics; population genetics; restoration genetics; restoration monitoring; restoration plantations; tropical forest restoration